Level of Local Community Brand Awareness of Samosir Tourism - Nur Cahaya Bangun; Jhonson Pardosi; Ilham Mirzaya Putra (International Journal of Applied Sciences in Tourism and Events, 2021)
This study aims to: (1) determine the level of local community brand awareness of the brand "Negeri Indah Kepingan Surga" in Samosir Regency, and (2) know the local community's perception of the branding "Negeri Indah Kepingan Surga" in Samosir Regency. Methods of data collection through questionnaires and interviews. Data analysis was carried out in descriptive quantitative with a Likert scale and  qualitative.  In  order  for  qualitative research  to  be better,  member checks and group discussion forums were then carried out. The sample in this study amounted to 96 people, while the informants amounted to 9 people. The results of this study are: (1) the level of brand awareness of the local community towards the brand "Negeri Indah Kepingan Surga" in Samosir Regency is at the brand recall level, and (2) There has not been any unified perception among the local community on the brand "Negeri Indah Kepingan Surga". in Samosir Regency. Some of the ways that must be done in order to achieve brand awareness of local community. The local community's perception of the tourism brand in Samosir Regency is still varied, although it has a positive tone.